2016
DOI: 10.1371/journal.pone.0160073
|View full text |Cite
|
Sign up to set email alerts
|

Molecular Scanning and Morpho-Physiological Dissection of Component Mechanism in Lens Species in Response to Aluminium Stress

Abstract: Aluminium (Al) stress was imposed on 285 lentil genotypes at seedling stage under hydroponics to study its effects on morpho-physiological traits where resistant cultigens and wilds showed minimum reduction in root and shoot length and maximum root re-growth (RRG) after staining. Molecular assortment based on 46 simple sequence repeat (SSR) markers clustered the genotypes into 11 groups, where wilds were separated from the cultigens. Genetic diversity and polymorphism information content (PIC) varied between 0… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
39
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4
2
1

Relationship

2
5

Authors

Journals

citations
Cited by 14 publications
(43 citation statements)
references
References 74 publications
4
39
0
Order By: Relevance
“…APX is one of the highly regulated enzymes [88]. In our previous studies also, we have identified significant increase in GPX activity in wild lentil genotypes [7]. For organic acids synthesis pathway, several genes were significantly up-regulated in wild genotype, one being that of Aconitatehydratase (Aco).…”
Section: Functional Allocation Of Degsmentioning
confidence: 81%
See 3 more Smart Citations
“…APX is one of the highly regulated enzymes [88]. In our previous studies also, we have identified significant increase in GPX activity in wild lentil genotypes [7]. For organic acids synthesis pathway, several genes were significantly up-regulated in wild genotype, one being that of Aconitatehydratase (Aco).…”
Section: Functional Allocation Of Degsmentioning
confidence: 81%
“…Three divergent lentil genotypes viz. L-4602, Barimasur-4 (BM-4) and ILWL-15 were used in this study [7]. First two accessions belong to Lens culinaris, whereas third belongs to Lens nigrican.…”
Section: Materials and Methods Plant Materialsmentioning
confidence: 99%
See 2 more Smart Citations
“…Thereby, to develop Al stress tolerant cultivars, an in depth understanding of divergent resistance mechanisms operating in lentil is crucial. Initial effort towards understanding these mechanisms in Lens species has revealed pattern II exclusion mechanism as one of the components, where secretion of citrate and malate from roots were observed which prevented binding of Al to extracellular and intracellular substances of the roots [7,8]. Further, secretion of exudates was found to be highest in wild genotypes [7].…”
Section: Introductionmentioning
confidence: 99%